MODERN APPROACHES TO FINANCIAL PROVISION OF INNOVATIVE DEVELOPMENT AGRARIAN SECTOR - Sus, T.Yo. (The actual problems of regional economy development, 2019)
In the condition of reforming the agrarian sector, Ukraine faces the problem of choosing an innovative development strategy and sources of its financing. The purpose of the research is to provide theoretical substantiation of scientific and methodological approaches and practical recommendations as to the concept of financial support of innovative development of the agricultural sector. The monographic method made it possible to point out that the countries with resource economies have low demand for innovations, that is, the absence of competitive industrial production does not create the basis for the formation of innovative environment and potential consumers of innovations. The domination of types of activities with diminishing return leads to the implementation of a model whereby public finances should be directed towards the implementation in the agricultural sector of tasks for its sustainable development in the conndition of growing demand for food and the need to preserve soil fertility, develop mechanisms of preferred financing and implementation these priorities. Modern approaches to financing innovative development are considered. It was noted that in the resource economies, innovations are aimed at increasing the production of raw materials and growing crops that has demand in the international markets. The domination of the activities with diminishing return does not allow financing of innovative development in a proper way both for the government’s part and the part of potential consumers of innovative products. It is proposed to combine for the agrarian sector of Ukraine two models where the model “government-investor” is used in innovations that has a greater social impact (such as eco-innovations) and vice versa the model “government-regulator” in innovation, which has a discernable economic effect. The specifics of innovative processes in the agricultural sector are outlined. The modern approaches to financial support of innovative development and factors that negatively influence the development of agro-innovation in Ukraine are analyzed.